Evidence of large-scale energy cascade in the spiral galaxy NGC 5236 - Nandakumar M.; Dutta P. (My University, 2025)
Turbulence plays an important role in the structure and dynamics of the galaxy and influences various processes therein including star formation. In this work, we investigate the large-scale turbulence properties of the external spiral galaxy NGC 5236. We combine the Very Large Array (VLA) multiconfiguration archival data with the new GMRT observation to estimate the column density and line-of-sight velocity fluctuation power spectra for this galaxy over almost two decades of length scales. The energy input scale to the interstellar medium turbulence is found to be around 6 kpc. Power spectra of the two-dimensional turbulence in the galaxy’s disc follow a power law with a slope −1.23 ± 0.06 for the column density and −1.91 ± 0.08 for the line-of-sight velocity. The measured power spectra slopes strongly suggest in favour of a compressive forcing with a steady energy input of ∼7 × 10−11 erg cm −2 s−1. We conclude that much of these originate from the gravitational instabilities and self-gravity in the disc. This is the first and most comprehensive study of turbulence statistics for any external spiral galaxy. © 2020 The Author(s)